2009
DOI: 10.1016/j.cub.2009.01.059
|View full text |Cite
|
Sign up to set email alerts
|

Sex Recognition through Midflight Mating Duets in Culex Mosquitoes Is Mediated by Acoustic Distortion

Abstract: Sexual recognition through wing-beat frequency matching was first demonstrated in Toxorhynchites brevipalpis, where wing-beat frequencies of males and females are similar. Here we show frequency matching in Culex quinquefasciatus, where the wing-beat frequencies of males and females differ considerably. The wing-beat frequencies converge not on the fundamental but on the nearest shared harmonic (usually female's third and male's second). Frequencies in this range are, however, too high to elicit phasic sensory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
210
3
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(240 citation statements)
references
References 20 publications
14
210
3
3
Order By: Relevance
“…The distortion product with the highest intensity generated through this mechanism ( f 2 Ϫ f 1 ) falls within the FRA of this neuron, perhaps causing its response. Neural sensitivity to cochlear distortion products has been documented previously throughout the auditory system (Goldstein and Kiang, 1968;McAlpine, 2004;Abel and Kössl, 2009;Portfors et al, 2009) and has been proposed as a mechanism for providing sensory cues in communication Warren et al, 2009). …”
Section: Changing the Spectral Content Of Vocalizations Altered Neuramentioning
confidence: 94%
“…The distortion product with the highest intensity generated through this mechanism ( f 2 Ϫ f 1 ) falls within the FRA of this neuron, perhaps causing its response. Neural sensitivity to cochlear distortion products has been documented previously throughout the auditory system (Goldstein and Kiang, 1968;McAlpine, 2004;Abel and Kössl, 2009;Portfors et al, 2009) and has been proposed as a mechanism for providing sensory cues in communication Warren et al, 2009). …”
Section: Changing the Spectral Content Of Vocalizations Altered Neuramentioning
confidence: 94%
“…Rather than giving a comprehensive view on acoustic communication in mosquitoes, and on the role of the transducer machinery therein, we would like to concentrate on one particular example that showcases how the very periphery of hearing may preprocess and analyse sound. For three species it has been reported that the wingbeat-matching behavior results in a convergence of higher harmonics rather than of the fundamental frequencies [41,43,47]. In all three cases a match appears to be achieved around the second harmonic of the male wingbeat (M2) and the third harmonic of the female wingbeat (F3; Figure 1D).…”
Section: Current Biologymentioning
confidence: 67%
“…Males detect, locate and chase females by detecting, locating and chasing a female flight tone [40]. Both sexes, in turn, have been reported to respond to each other's wingbeat frequencies by modulating their own [41][42][43], an acoustic behavior thought to mediate male-female interactions within larger mating swarms. Just as in Drosophila, mosquito antennae have been reported to be active, nonlinear oscillators of exquisite nanometer-range sensitivity [23,[44][45][46], with the source of the observed activity and nonlinearity likely (A) When stimulated by pure tones at its best frequency, the wild-type Drosophila antennal receiver displays a compressive nonlinearity, which produces relatively larger displacements for smaller stimuli (particle velocities), depicted by the green curve.…”
Section: The Sensory Periphery Of Diptera Auditory Anatomy and Generamentioning
confidence: 99%
See 2 more Smart Citations